11 years of tracking aid to reproductive, maternal, newborn, and child health: estimates and analysis for 2003–13 from the Countdown to 2015 - Grollman, Christopher (Lancet Glob Health, 2016)
BACKGROUND: Tracking aid flows helps to hold donors accountable and to compare the allocation of resources in relation to health need. With the use of data reported by donors in 2015, we provided estimates of official development assistance and grants from the Bill & Melinda Gates Foundation (collectively termed ODA+) to reproductive, maternal, newborn, and child health for 2013 and complete trends in reproductive, maternal, newborn, and child health support for the period 2003–13. METHODS: We coded and analysed financial disbursements to reproductive, maternal, newborn, and child health to all recipient countries from all donors reporting to the creditor reporting system database for the year 2013. We also revisited disbursement records for the years 2003–08 and coded disbursements relating to reproductive and sexual health activities resulting in the Countdown dataset for 2003–13. We matched this dataset to the 2015 creditor reporting system dataset and coded any unmatched creditor reporting system records. We analysed trends in ODA+ to reproductive, maternal, newborn, and child health for the period 2003–13, trends in donor contributions, disbursements to recipient countries, and targeting to need. FINDINGS: Total ODA+ to reproductive, maternal, newborn, and child health reached nearly US$14 billion in 2013, of which 48% supported child health ($6·8 billion), 34% supported reproductive and sexual health ($4·7 billion), and 18% maternal and newborn health ($2·5 billion). ODA+ to reproductive, maternal, newborn, and child health increased by 225% in real terms over the period 2003–13. Child health received the most substantial increase in funding since 2003 (286%), followed by reproductive and sexual health (194%), and maternal and newborn health (164%). In 2013, bilateral donors disbursed 59% of all ODA+ to reproductive, maternal, newborn, and child health, followed by global health initiatives (23%), and multilateral agencies (13%). Targeting of ODA+ to reproductive, maternal, newborn, and child health to countries with the greatest health need seems to have improved over time. INTERPRETATION: The increase in reproductive, maternal, newborn, and child health funding over the period 2003–13 is encouraging. Further increases in funding will be needed to accelerate maternal mortality reduction while keeping a high level of investment in sexual and reproductive health and in child health. FUNDING: Subgrant OPP1058954 from the US Fund for UNICEF under their Countdown to 2015 for Maternal, Newborn and Child Survival Grant from the Bill & Melinda Gates Foundation.